The Impact of Generosity on Church Growth and Development: Insights from World Revival Faith Ministry, Lagos, Nigeria - Ayomide Joseph Soneye; Adeniyi oluwafemi Abodunrin; Timothy O.A Yerokun; Adetayo Olorunlana (Matondang Journal, 2026)
This study explores the role of generosity in driving the growth and development of World Revival Faith Ministry (WRFM) in Lagos, Nigeria, between 2010 and 2025. Adopting a qualitative methodology that combines documentary analysis with the authors’ firsthand experiences, the research investigates how generosity, manifested through financial giving, resource sharing, and service has catalyzed WRFM’s spiritual, organizational, and community advancements. Findings highlight that substantial contributions from key donors, especially the General Overseer, have enabled initiatives such as evangelism, missionary outreach, educational scholarships, business empowerment, and community development projects. These efforts have expanded membership, strengthened leadership, and increased the church’s social impact. The study also identifies challenges, including reliance on a limited donor base, sustainability concerns, and the need for enhanced financial transparency and broader member participation. Opportunities for growth include diversifying funding sources, fostering leadership development, and engaging in strategic partnerships. The research underscores the transformative power of generosity in faith-based organizations, emphasizing its significance in achieving sustainable growth and meaningful community engagement. Providing actionable recommendations such as cultivating a culture of holistic generosity, promoting financial accountability, and integrating community-focused initiatives, the study offers valuable insights for church leaders and policymakers. This work contributes to the limited empirical research on the intersection of generosity and church development in African contexts, presenting WRFM as a case study for leveraging stewardship and philanthropy to achieve spiritual and societal relevance.